2001
DOI: 10.1074/jbc.m107323200
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-promoted Internalization of a Ternary Complex between Calcitonin Receptor-like Receptor, Receptor Activity-modifying Protein 1 (RAMP1), and β-Arrestin

Abstract: The calcitonin receptor-like receptor (CRLR) is a seven-transmembrane domain (7TM) protein that requires the receptor activity-modifying protein 1 (RAMP1) to be expressed at the cell surface as a functional calcitonin gene-related peptide (CGRP) receptor. Although dimerization between the two molecules is well established, very little is known concerning the trafficking of this heterodimer upon receptor activation. Also, the subcellular localization and biochemical state of this ubiquitously expressed protein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
97
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(111 citation statements)
references
References 48 publications
12
97
2
Order By: Relevance
“…First-strand cDNA was synthesized from 1 g of total RNA using a mixture of oligo(dT) [12][13][14][15][16][17][18] and random hexamer primers and Superscript Reverse Transcriptase (Invitrogen Life Technologies). For amplification, the qPCR Mastermix Plus for SYBR Green I without UNG (Eurogentec) was used to detect accumulation of PCR products during cycling on an Applied Biosystems 7300 cycler.…”
Section: Analysis Of Cytokine Mrna and Protein Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…First-strand cDNA was synthesized from 1 g of total RNA using a mixture of oligo(dT) [12][13][14][15][16][17][18] and random hexamer primers and Superscript Reverse Transcriptase (Invitrogen Life Technologies). For amplification, the qPCR Mastermix Plus for SYBR Green I without UNG (Eurogentec) was used to detect accumulation of PCR products during cycling on an Applied Biosystems 7300 cycler.…”
Section: Analysis Of Cytokine Mrna and Protein Productionmentioning
confidence: 99%
“…Alternatively, the CGRP receptor may activate phospholipase C-␤1 via G␣ q/11 proteins, causing calcium mobilization (13). Following prolonged CGRP exposure, internalization of a ternary complex between CRLR-RAMP1 and ␤-arrestin through clathrincoated pit-mediated endocytosis was observed (14).…”
mentioning
confidence: 99%
“…However neither RAMP2 nor RAMP3 is known to change the glycosylation pattern to a significant loss in CGRP potency despite normal trafficking of the receptor complex to the plasma membrane (Hilairet et al, 2001). Studies have also shown that the CLR, RAMP1 and arrestins can exist in a ternary complex in HEK 293 cells (Hilairet et al, 2001).…”
Section: Calcitonin Like-receptor and Rampsmentioning
confidence: 99%
“…Studies have also shown that the CLR, RAMP1 and arrestins can exist in a ternary complex in HEK 293 cells (Hilairet et al, 2001). This has led to the suggestion that RAMPs can associate with the CLR throughout its entire life cycle being an essential component of the desensitisation and internalisation machinary.…”
Section: Calcitonin Like-receptor and Rampsmentioning
confidence: 99%
See 1 more Smart Citation